Analisis Implementasi Kebijakan Reformasi Birokrasi Terhadap Kinerja Pegawai Negeri Sipil di Lingkup Dinas Perhubungan Kota Pare-Pare - Anne Abdurachman (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Bureaucratic reform is a government effort to improve the performance of state apparatus to provide optimal service to the community. This study aims to analyze the implementation of bureaucratic reform policies on the performance of Civil Servants (PNS) at the Pare-Pare City Transportation Agency. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of bureaucratic reform at the Pare-Pare City Transportation Agency has gone quite well, but there are still several obstacles such as limited human resources and supporting facilities and infrastructure. The bureaucratic reform policy has proven to have a positive effect on improving the performance of PNS in terms of productivity, service quality, responsiveness, responsibility, and accountability. Strong commitment from leaders and all employees is needed as well as adequate budget support to optimize the implementation of bureaucratic reform in the future.